Jurnal Perempuan Edisi 111, Vol 27. No. 1, Edisi 112, Vol 27. No. 2, Edisi 113, Vol 27. No 3. - Andri Rahman (Yayasan Jurnal Perempuan, 2022)
Indeks Jurnal Perempuan Edisi 111, Vol 27. No. 1, Edisi 112, Vol 27. No. 2, Edisi 113, Vol 27. No 3.